AN ANALYSIS OF THE VERBAL COMMUNICATION OF PEER COUNSELORS IN PERFORMING ONLINE COUNSELING SERVICES - Meliyawati; Ajeng Muliasari (Jurnal PAJAR (Pendidikan dan Pengajaran), 2020)
This study focused on an analysis of the verbal communication of peer counselors in performing online counseling services in the pandemic phase in Indonesia. This study utilized a qualitative research approach with analytical descriptive, referring to a method to obtain a view systematically, factually, and accurately related to the facts and properties of the objects into which the research focused. Then, the results of the findings were analyzed and interpreted to draw conclusions. The online peer counseling services were performed by students of BK UNMA for two weeks. The services were available by using some social media. The online peer counseling services focused on interpersonal communication processes through communication channels. Results indicated that in performing online counseling services, the counselors used several verbal communication techniques, such as invitations to start, reception or showing understanding, reflection of mind, reflection of feelings, clarification of messages, feedback, alternative presentations, inquiries, interpretations, diagnosis, support or guidance, and suggestions. These techniques were performed based on the dominant issues faced by the clients, which were related to self-confidence or insecurity, as well as family and employment problems.